2005
DOI: 10.1021/ja044531p
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β-Protein:  Monomer Structure and Early Aggregation States of Aβ42 and Its Pro19Alloform

Abstract: The amyloid beta-protein (Abeta) is a seminal neuropathic agent in Alzheimer's disease (AD). Recent evidence points to soluble Abeta oligomers as the probable neurotoxic species. Among the naturally occurring Abeta peptides, the 42-residue form Abeta42 is linked particularly strongly with AD, even though it is produced at approximately 10% of the levels of the more abundant 40-residue form Abeta40. Here, we apply mass spectrometry and ion mobility to the study of Abeta42 and its Pro19 alloform. The Phe19 --> P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

32
430
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(465 citation statements)
references
References 59 publications
32
430
2
1
Order By: Relevance
“…This study indicated differences in the oligomers formed from A␤1-42 compared with those formed from A␤1-40, two species that adopt similar random coil structures in solution, although A␤1-42 forms amyloid fibrils significantly faster than A␤1-40 [44,60]. In vitro, A␤1-42 showed evidence for dimer, tetramer, hexamer, and dodecamer oligomers, whilst only the dimer and tetramer were detected in the case of A␤1-40, thus offering plausible insights into why their contribution to amyloidosis is quite different (Figure 3).…”
Section: Are Oligomers Amyloid Intermediates or Dead-end Products Andmentioning
confidence: 87%
See 1 more Smart Citation
“…This study indicated differences in the oligomers formed from A␤1-42 compared with those formed from A␤1-40, two species that adopt similar random coil structures in solution, although A␤1-42 forms amyloid fibrils significantly faster than A␤1-40 [44,60]. In vitro, A␤1-42 showed evidence for dimer, tetramer, hexamer, and dodecamer oligomers, whilst only the dimer and tetramer were detected in the case of A␤1-40, thus offering plausible insights into why their contribution to amyloidosis is quite different (Figure 3).…”
Section: Are Oligomers Amyloid Intermediates or Dead-end Products Andmentioning
confidence: 87%
“…In contrast, the A␤1-40 tetramer was found to have a smaller collision cross-section indicating a more closed structure, which would not be disposed to the addition of either a monomer or a dimer and hence explaining why there was no evidence of the hexamer or any higher order species for A␤1-40. From these [44] and earlier [60] ESI-IMS-MS oligomer data, a global scheme of amyloid-␤ oligomerization was proposed in which the A␤1-42 tetramer added a dimer to produce the ring-shaped hexamer, which subsequently dimerized to produce a two-ring, stacked dodecamer ( Figure 3). Following this, it was suggested that the dodecamer underwent rearrangement, added more monomers and formed ␤-sheet fibrils.…”
Section: Are Oligomers Amyloid Intermediates or Dead-end Products Andmentioning
confidence: 96%
“…Coupling to MS and to electrospray (ESI) and matrix-assisted laser desorption ionization (MALDI) ion sources in the 1990s (8,9) brought IMS to biological analyses (2,4,6). In particular, peptide and protein folding (2,4,(9)(10)(11)(12)(13)(14) and amyloidogenic misfolding (15) were explored. Application of IMS and IMS/MS is expanding to ever-larger macromolecules, including noncovalent assemblies with mass (m) Ͼ 1 MDa (16)(17)(18).…”
mentioning
confidence: 99%
“…Application of IMS and IMS/MS is expanding to ever-larger macromolecules, including noncovalent assemblies with mass (m) Ͼ 1 MDa (16)(17)(18). Such studies have used both drift tube (DT) IMS (1)(2)(3)(4)(5)(7)(8)(9)(10)(11)(12)(13)(14)(15) and differential mobility analyzers (DMA) (17,18) to separate ions by absolute mobility (K). In DT IMS, ions are separated while being pulled through still gas by an electric field.…”
mentioning
confidence: 99%
“…One of the important recent applications of the IMS-MS is the investigation of protein folding in neurodegenerative diseases [13]. Additionally, since homologous series of different compounds usually show different structural densities, displaying an m/z versus mobility diagram gives a very practical overview of the compound groups being studied, independent of secondary mass spectrometric investigations, e.g., collision induced dissociation (CID).…”
mentioning
confidence: 99%